PENERAPAN TERAPI PURSED LIPS BREATHING PADA AN.S USIA SEKOLAH 12 TAHUN YANG MENGALAMI GANGGUAN FREKUENSI NAFAS AKIBAT ASMA DI RUANG MELATI RUMAH SAKIT TK.II DUSTIRA CIMAHI - Zulva, Siti; Gustami, Ferdy (Jurnal Kesehatan An-Nuur, 2025)
Asthma is a heterogeneous disease that is usually characterized by chronic inflammation of the respiratory tract. characterized by a history of respiratory symptoms such as wheezing, shortness of breath, tightness in the chest, and coughing whose intensity varies from time to time and limited exhaled air flow, apart from that, asthma is often encountered in childhood at school age 6-12 years. WHO and the Global Asthma Network (GAN), the world asthma organization, estimate that by 2025, the number of asthma sufferers will increase by 400 million and cause 250,000 deaths (WHO, 2023). The Ministry of Health noted that by the end of 2020, asthma will be one of the most common diseases affecting Indonesian society, covering 4.5% of Indonesia's total population (more than 12 million people). In 2019, WHO estimates that the number of asthma sufferers will reach 235 million people, representing 1-18% of the world's population (Aufa et al., 2023). The pursed lips breathing exercise is a way to position pursed lips. This technique increases alveolar pressure in each lung lobe, thereby increasing air flow during expiration and improving oxygen status (Oktaviani et al., 2021). The Pursed lips breathing technique is carried out for 15 minutes with 5 inhales and 5 exhales, with a 2 second pause between cycles. Significant differences in oxygen status were observed before and after lip breathing. The pursed lips breathing technique has been proven to be a non-pharmacological therapy that can be used routinely to improve oxygen status in children with asthma, thereby optimizing lung mechanical function (Oktaviani et al., 2021). From this research, it can be concluded that non-pharmacological therapy using the pursed lips breathing technique succeeded in increasing oxygen saturation significantly every day. The results of the study showed that the development of the respiratory system increased after being given pursed lips breathing therapy. Assessment of the development of respiration and Spo2 before applying PLB respiration was 35x/minute, Spo2 89% and after applying PLB respiration became 28x/minute, Spo2 97%. This means that applying PLB by inhaling air from the nose and exhaling through the mouth with the mouth closed is very effective in increasing oxygen saturation and improving respiration in 12 year old school aged An.S.